Effect of moisture conservation practices on performance of cluster bean under rainfed condition - PAREEK, N. K.; GODARA, S. L.; KUMAR, ANAND; RAKESH, SHRI; KUMAWAT, AMIT (Journal of Soil and Water Conservation, 2022)
Field experiment was conducted during kharif seasons to study the effect of moisture conservation practices on performance of cluster bean varieties in rainfed condition. The 12 treatment combinations comprised of four moisture conservation practices (30 cm row spacing, 60 cm row spacing, 60 cm row spacing along with earthing by hand plough at 25 & 35 DAS and 60 cm row spacing along with hoeing by wheel hoe at 25 & 35 DAS) in main plot and three varieties of cluster bean (RGC-936, RGC-1003 and RGC-1066) in sub plots were laid out in split plot design with four replications. On the basis of two years pooled data, results revealed that 60 cm row spacing along with earthing by hand plough at 25 & 35 DAS recorded higher plant height (164.15cm), dry matter accumulation (24.52 g/plant), more number of pods per plant (63.5), seed (618.1 kg/ha) and straw (2268.33 kg/ha) yield, proline content (0.269 mg/g), membrane stability index (24.7%) and relative water content (67.0%) as compared to rest of moisture conservation treatments. Further, results shows that variety RGC 1066 recorded higher values of plant height (157.67 cm), dry matter accumulation (23.51 g/plant), more number of pods per plant (68.9), number of seeds per pod (6.6) seed (631.7 kg/ha) and straw (2281.81 kg/ha) yield, proline content (0.332 mg/g), membrane stability index (24.2%) and relative water content (67.5%).